1999
DOI: 10.1002/(sici)1097-0177(199910)216:2<96::aid-dvdy2>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of avian craniofacial muscles: I. Patterns of early regulatory gene expression and myosin heavy chain synthesis

Abstract: Myogenic populations of the avian head arise within both epithelial (somitic) and mesenchymal (unsegmented) mesodermal populations. The former, which gives rise to neck, tongue, laryngeal, and diaphragmatic muscles, show many similarities to trunk axial, body wall, and appendicular muscles. However, muscle progenitors originating within unsegmented head mesoderm exhibit several distinct features, including multiple ancestries, the absence of several somite lineage-determining regulatory gene products, diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 0 publications
8
81
0
1
Order By: Relevance
“…The locations of extraocular and branchial muscle precursors identified in this study correlate well with the sites of activation of muscle-specific transcription factors, e.g., Myf5 and MyoD (Hacker and Guthrie, 1998;Noden et al, 1999;Mootoosamy and Dietrich, 2002). They are concordant with transplantation-based maps by Noden (1983b) and add finer definition to the boundaries of individual myogenic foci.…”
Section: Muscle Originssupporting
confidence: 69%
See 2 more Smart Citations
“…The locations of extraocular and branchial muscle precursors identified in this study correlate well with the sites of activation of muscle-specific transcription factors, e.g., Myf5 and MyoD (Hacker and Guthrie, 1998;Noden et al, 1999;Mootoosamy and Dietrich, 2002). They are concordant with transplantation-based maps by Noden (1983b) and add finer definition to the boundaries of individual myogenic foci.…”
Section: Muscle Originssupporting
confidence: 69%
“…Previous mapping and gene expression studies have shown that skeletal muscle progenitors form aggregates at or close to their sites of origin within paraxial mesoderm (Noden, 1983b;McClearn and Noden, 1988;Noden et al, 1999). Retroviral injections confirm that progenitors of extraocular muscles first condense, then move as cohorts toward the mesoderm:crest interface, and subsequently enter the crest-derived periocular environment.…”
Section: Lineage-specific Movements Of Paraxial Mesoderm Cellsmentioning
confidence: 70%
See 1 more Smart Citation
“…The coexpression of MyoD and MyoR in the developing head may explain why terminal differentiation in the head is delayed relative to the axial muscles (see Fig. 2; Noden et al, 1999). Therefore, one simple hypothesis is that loss of Tbx1 function results in the increase of a factor (MyoR) that represses myogenesis-hence, the hypoplasia of the branchial arch muscles.…”
Section: Discussionmentioning
confidence: 99%
“…1). Somites are found throughout the chordates and are the source of all the skeletal muscle of the trunk and limbs as well as some head muscles, such as the tongue muscles (Noden et al 1999, Brent & Tabin 2002, Christ et al 2007. Somites begin forming at the anterior of the embryo and are added posteriorly as the embryo extends.…”
Section: Myogenesis In Somitesmentioning
confidence: 99%